2008
DOI: 10.1002/ijc.24067
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 cytotoxin has potent antitumor activity and synergizes with paclitaxel in a mouse model of oral squamous cell carcinoma

Abstract: Interleukin-13 receptor-targeted cytotoxin (IL13-PE38) is highly cytotoxic to certain types of human cancers expressing abundant levels of IL-13Ralpha2 chain. Although IL13-PE38 is being tested in a Phase III clinical trial in brain tumors, the activity of IL13-PE38 alone or when combined with taxane, a chemotherapeutic drug for oral squamous cell carcinoma (OSCC), has not been investigated. Here, we show that approximately 40% of OSCCs (n = 50) in a tissue array are strongly positive for IL-13Ralpha2, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…IL-13Rα2, one of the IL-13 receptors, is highly expressed in some cancer cells, including GBM23 and OSCC24; therefore, targeting this receptor, such as CAR-T and IL13-PE, would be new strategy for these cancer patients25. Interestingly, recent reports have shown that macrophages recruited by inflammation in ulcerative colitis and pulmonary fibrosis also express IL-13Rα22627.…”
Section: Resultsmentioning
confidence: 99%
“…IL-13Rα2, one of the IL-13 receptors, is highly expressed in some cancer cells, including GBM23 and OSCC24; therefore, targeting this receptor, such as CAR-T and IL13-PE, would be new strategy for these cancer patients25. Interestingly, recent reports have shown that macrophages recruited by inflammation in ulcerative colitis and pulmonary fibrosis also express IL-13Rα22627.…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that IL13-PE combined with paclitaxel mediated potent antitumor effects in vitro and in vivo in a mouse tumor model of human oral squamous cell carcinoma (40) and, combined with gemcitabine, it mediated synergistic antitumor effects and prolonged the survival of animals in a pancreatic cancer model (41). In this study, we showed that IL13-PE may act as a strong immune stimulant and synergize with IL-13Rα2 DNA vaccine in inhibiting tumor growth and prolonging the survival of animals with established breast cancer or sarcoma tumors.…”
Section: Discussionmentioning
confidence: 94%
“…178 Hosmer et al in 2012, studied mesophase lamellar LCs formed with glycerides for the incorporation of the anticancer drug paclitaxel. 184 Paclitaxel is highly effective against various types of cancer, including oral cancer; [185][186][187] however, it has severe adverse effects associated with systemic drug administration, including hypersensitivity reactions, thrombocytopenia, and neutropenia. 188,189 Hosmer et al 184 found that, among the formulations studied, the Brij-based lamellar phase containing 20% medium-chain …”
Section: Liquid Crystalsmentioning
confidence: 99%